(untitled) (Forum for Linguistic Studies, 2024)
Sheikh Sukban Al-Ali is considered one of the most prominent tribal figures in the history of Al-Muntaq district, and Iraq in general, not only for his stance on tribal issues but also for his national and political positions during the late Ottoman period, the British occupation of Iraq (1914-1920), and the royal era (1921-1958). This research explores the role of Sukban Al-Ali in the Al-Karadi Uprising of 1936. Due to this uprising, a policy of inequality among tribal leaders was implemented by the government of Yasin Al-Hashimi towards most of the Al-Muntaq tribes. This policy led to uprisings among several tribes of Al-Muntaq. Tribal alliances were the core of the uprising, with its first alliance being formed with Sukban Al-Ali, the chief of the Khafaja tribe, who pledged to control the road between the cities of Nasiriyah and Shatra. The research also covers the attempts of the Al-Muntaq district administrator to win over Sukban Al-Ali to the government’s side, but it was only successful after military force was directed towards Al-Karadi, leading all tribes to declare their surrender to the government’s orders.